Allocation Priority Determination System for Provincial Bridge Maintenance Fund in Special Region of Yogyakarta By Examining Physical Conditions, Operational Cost and Volume of Traffic - Rifqi Aulia Abdillah; Sholihin As’ad; Senot Sangadji (Universitas Sebelas Maret, 2017)
The maintenance of bridges is relatively expensive. Those may lead the maintenance program into a classical problem which is limited of the fund. Therefore, the priority level of bridges maintenance is needed in order to attain an effective and efficient fund usage toward prevalent condition of every bridges in Special Region of Yogyakarta. The objective of this research was to provide the maintenance fund for provincial bridges in Special Region of Yogyakarta. The research covered 10 bridges in Special Region of Yogyakarta. The Assessments method for bridge physical condition was based on guide of Bridge Management System (BMS). As the bridge physical condition was known, the maintenance measure and its needed maintenance cost can be determined. The allocation of fund for each bridge was calculated based on Dynamic Programming Method. The result can be draw that by 5 million rupiah the maintenance fund for each of those 10 bridge of Yogyakarta Special Region is 5 million rupiah for Demak Ijo Bridge, 13 million rupiah for Bedingin Bridge, 10 million rupiah for Denggung Bridge, 5 million rupiah for Ngentak Bridge, 5 million rupiah for Karang Semut Bridge, 8 million rupiah for 2rd Kronggahan Bridge, 7 million rupiah for Besi Bridge, 8 million rupiah for Cebongan Bridge, 2 million rupiah for Kembang Songo Bridge, 2 million rupiah for 1st Kronggahan Bridge. Those allocation system provide 78,7% an average percentage on provincial bridges in Special Region of Yogyakarta.